2020
DOI: 10.1039/d0cp01619e
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the protonic conductivity of porous yttria-stabilized zirconia thin films by surface modification

Abstract: Porous yttria-stabilized zirconia (YSZ) thin films were prepared by pulsed laser deposition to investigate the influence of specific surface area on the electrical and protonic transport properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 75 publications
2
22
0
Order By: Relevance
“…29). An amorphous-to-crystalline phase transition with increasing layer thickness has also been reported by Celik et al 129 They coated porous YSZ thin films by ALD of TiO 2 . While the deposition of 6 nm TiO 2 resulted in the formation of amorphous material, a crystalline coating (anatase TiO 2 ) was found for a thickness of approx.…”
Section: Surface Modificationsupporting
confidence: 66%
See 2 more Smart Citations
“…29). An amorphous-to-crystalline phase transition with increasing layer thickness has also been reported by Celik et al 129 They coated porous YSZ thin films by ALD of TiO 2 . While the deposition of 6 nm TiO 2 resulted in the formation of amorphous material, a crystalline coating (anatase TiO 2 ) was found for a thickness of approx.…”
Section: Surface Modificationsupporting
confidence: 66%
“…However, it is now widely accepted that the increased conductivity arises from protons moving in chemisorbed and physisorbed water layers along the pores and surface of nanostructured oxides. 100,104,[127][128][129][130] The strong dependence of the protonic conductivity on relative humidity and temperature is related to the structure of the adsorbed water molecules, as summarized by Stub et al 131 The structure of the water layer on TiO 2 is schematically shown in Fig. 11.…”
Section: Protonic Conductivitymentioning
confidence: 97%
See 1 more Smart Citation
“…However, adsorption of salivary enzymatic molecules on the polished surface also propose another underlying mechanism together with the nano surface roughness [ 17 ], as polishing involves breakage of surface bonds when the material is removed, as a result the surface nature is altered; transforming the surface, which we initially thought as dull and monotonous attraction towards uptake of salivary biomolecules. It is recognized that proteins tend to adhere more strongly to non- polar than to polar, to high surface tension than to low surface tension, and to charged than to uncharged substrates [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the influence of an ultrathin surface coating with varying thickness on the electrochemical performance, NCM samples were coated with a thin Al 2 O 3 film using atomic layer deposition (ALD), which enables a homogeneous coating even of porous samples. [66,67,88] The ALD deposition was carried out in a PicoSun R200 ALD reactor using trimethylaluminium (TMA, STREM chemicals inc., min. 98%) as precursor and deionized water as reactant for TMA to form the oxide layer.…”
Section: Methodsmentioning
confidence: 99%